Analysis of mercury and other heavy metals accumulated in lichen Usnea antarctica from James Ross Island, Antarctica - Zvěřina, O.; Láska, K.; Červenka, R.; Kuta, J.; Coufalík, P. (Pavel); Komárek, J. (Environmental Monitoring and Assessment, 2014)
The study was designed to investigate the content and distribution of selected heavy metals (As, Cd, Co, Cr, Cu, Hg, Mn, Ni, Fe, Pb and Zn) in samples of fruticose macrolichen Usnea antarctica from James Ross Island.